Novel TGF-β inhibitors ready for prime time in onco-immunology. (2nd January 2017) - de Gramont, Armand; Faivre, Sandrine; Raymond, Eric
ABSTRACT: Transforming Growth Factor (TGF)-β inhibitors have been in development for decades with the outmost results of being promising candidates. From the latest clinical results at the 2016 ASCO meeting converging evidences suggest that we have moved from promising to effective drug nominees.